Temperature Dependency of Proton Pumping Activity for Marine Microbial Rhodopsin from Antartic Ocean - Kim, Se-Hwan (Sci Rep, 2020)
Proteorhodopsin (PR) is discovered from marine bacteria and it has proton pumping activity from inside to outside of the cell using light energy. In general, PR classified into two groups by the maximum absorption spectra. In this study, we isolated the two of a full sequence of opsin homologues by PCR from the seawater sample near King George Island, Antarctica. One was the same sequence as the first reported GPR (Green-light absorbing PR) from Monterey Bay. Another named HSG119 was a newly discovered sequence which shows high sequence similarity with BPR (Blue-light absorbing PR). HSG119 has an absorption maximum at 493 nm with broader spectrum at pH7.0 and it can pump protons out of the cell membrane. Interestingly, it showed a similar temperature dependence to GPR(Y200N) that isolated near the North pole.